2018
DOI: 10.5009/gnl18072
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Dendritic Cells Induced by Mesenchymal Stem Cells Ameliorate Dextran Sodium Sulfate-Induced Chronic Colitis in Mice

Abstract: Background/AimsRegulatory dendritic cells (rDCs), which can be induced by mesenchymal stem cells (MSCs), play an important role in inducing and maintaining homeostasis of regulatory T cells and exhibit anti-inflammatory functions. In this study, we investigated whether MSCs could differentiate DCs into rDCs and compared the therapeutic effects of rDCs and MSCs on dextran sodium sulfate (DSS)-induced chronic colitis mice.MethodsImmature DCs (imDCs) and lipopolysaccharide (LPS)-treated mature DCs (mDCs) were co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
(31 reference statements)
0
22
0
1
Order By: Relevance
“…Some studies indicated that adoptive transfer of bone marrow-derived DCs exacerbated DSS-induced colitis in mice, while selective genetic ablation of DCs attenuated the severity of colitis. This hinted that DCs are critical in pathogenetic process of DSS-induced colitis, and anti-DC therapy can effectively block inflammatory cells infiltration to the inflamed colon and inhibit inflammation to protect against DSS colitis (Berndt et al, 2007;Massafra et al, 2015;Jo et al, 2018). It has been shown that inflammatory DCs can induce Th1 and Th17 cell response, inhibit the T regulatory cell function, and lead to imbalance between pro-inflammatory and anti-inflammatory factors, as well as induce epithelial cell damage and colitis (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicated that adoptive transfer of bone marrow-derived DCs exacerbated DSS-induced colitis in mice, while selective genetic ablation of DCs attenuated the severity of colitis. This hinted that DCs are critical in pathogenetic process of DSS-induced colitis, and anti-DC therapy can effectively block inflammatory cells infiltration to the inflamed colon and inhibit inflammation to protect against DSS colitis (Berndt et al, 2007;Massafra et al, 2015;Jo et al, 2018). It has been shown that inflammatory DCs can induce Th1 and Th17 cell response, inhibit the T regulatory cell function, and lead to imbalance between pro-inflammatory and anti-inflammatory factors, as well as induce epithelial cell damage and colitis (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that adoptive transfer of bone marrow-derived DCs exacerbated DSS-induced colitis in mice, while selective genetic ablation of DCs attenuated the severity of colitis. This hinted that DCs are critical in pathogenetic process of DSS-induced colitis, and anti-DC therapy can effectively block inflammatory cells infiltration to the inflamed colon and inhibit inflammation to protect against DSS colitis ( Berndt et al, 2007 ; Massafra et al, 2015 ; Jo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the maturity of classical dendritic cells (cDCs) in the lungs of ALI mice increased significantly, while inhibition of DCs maturation reduced the inflammatory response and pathological damage in the lungs [12,13]. MSC induced mature DCs (mDCs) differentiation into regulatory DC (DCreg) with low expression of CD80 and CD86 DCreg, which induced the expression of CD4, CD25, and Foxp3 in primary splenocytes isolated from mice [14]. MSC also abrogated the capacity of mDC migration to CCL19, or for DC to display MHC class II peptide complexes recognized by specific antibody, or ovalbumin-pulsed DC to support antigen-specific CD4 + T cell proliferation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of the MSC-DCs in DSS-induced colitis mice causes colon tissue IL-6, IFN-γ, and TNF-α to decrease while Foxp3, IL-10, and TGF-β increase. This implicates that MSCs differentiate DCs into regulatory DCs, which ameliorate colitis [23] and also suppress inflammatory phenotype of DCs in a galectin-3-dependent manner [24]. It is also documented that the regulatory DCs further trigger the production of Tregs to enhance the anti-inflammatory effect of MSCs in immune disorders.…”
Section: Influence Of Mesenchymal Stem Cellsmentioning
confidence: 90%